Realitas Beban Ganda Perempuan di Balik Fleksibilitas UMKM Digital Rumahan - Alma Amelia Qotrunada; Jahra Pitriani; Mochammad Faudzan Arrasyid; Sri Damayanti (Journal Social Society, 2026)
This study examines home-based digital micro, small, and medium enterprises (MSMEs) operated by married women with domestic responsibilities, focusing on the relationship between economic activities, household labor, and household social structures. Using a descriptive qualitative approach, this study involved three married women in Bandung, West Java, who had children and had operated home-based digital businesses for at least six months through platforms such as WhatsApp and Instagram. Data were collected over one month through in-depth interviews, non-participant observation, and documentation, and were analyzed using data reduction, data presentation, conclusion drawing, and verification. The findings show that economic and domestic activities occur simultaneously within the same household space, blurring the boundaries between productive and reproductive work. Although the women contributed to household income, they continued to prioritize domestic responsibilities, indicating the persistence of gender-based divisions of labor within the household. Participation in digital MSMEs also increased women’s workload because business activities were carried out alongside childcare and household tasks. The flexibility offered by home-based digital work was largely illusory, as it related more to work location than to control over time and workload. Theoretically, this study contributes to economic sociology and gender studies by showing how digital economic activities are embedded in household social structures. Practically, the findings suggest that women’s MSME empowerment programs should not only focus on digital marketing and income generation, but also consider domestic workload, family support, and more equitable household role arrangements.